Peran Kepala Dalam Meningkatkan Pembangunan Kampung Darmorpis Darfuar Distrik Samofa Kabupaten Biak Numfor - Iswahyudi Iswahyudi; Agustina Agustina; Asmadianto Asmadianto; Edyanto Edyanto (Prosiding Seminar Nasional Ilmu Hukum, 2025)
This study aims to analyze the role of village heads in improving development in Darmorpis Village, Samofa District, Biak Numfor Regency. Village administration, as the spearhead of government administration, plays an important role in realizing public services, community empowerment, and sustainable development. This study uses qualitative methods with data collection techniques through interviews, observation, and literature study. The results show that the village head plays a strategic role in leading and mobilizing all elements of society, including traditional leaders, religious leaders, village officials, and the general public, to actively participate in development. The village head's leadership emphasizes not only administrative aspects but also service, motivation, work discipline, and capacity building for village officials. The synergy between leadership and community participation proved to be a key factor in the success of the development program in Darmorpis Village. However, this study also found obstacles in the form of a lack of coordination regarding the implementation of assistance programs from the local government, which had an impact on the community's perception of the effectiveness of development. Thus, it can be concluded that the success of village development is largely determined by the visionary leadership of the village head and the collective support of the community.